The emancipatory discourse in Carol Ann Duffy’s the World’s Wife - Abdulkadhim Mhana, Arsetim Zainab; Talif, Rosli; Jujar Singh, Hardev Kaur; Zainal, Zainor Izat (Maya Global Education Society, 2019)
Purpose: This study examines Carol Ann Duffy’s unique discourse of rewriting and telling old stories, fairy tales, and myths that represent female characters as marginalized, inactive, and weak. Methodology: A qualitative research design was adopted to investigate the pervasive shifts of restructuring female convictions, configurations, and identity in selected poems from Duffy’s The World’s Wife. The research data in this paper is drawn from two main sources: literary books and articles. Main Findings: The analysis unravels Duffy’s feminist attitude in her poetic collection to reveal how she used her poems as weapons to fight against female marginalization. Simultaneously, the study critiques the traditional patterns of feminist thinking with origins in history and myths that are still prevalent in Western culture. Applications: This paper can be used by literary scholars and students. Novelty/Originality: In this research, female characters were explored in the light of Simon de Beauvoir’s concept of the other from her book The Second Sex and Hélène Caxias’s critical notions postulated as écriture feminine.